2018
DOI: 10.1097/jte.0000000000000037
|View full text |Cite
|
Sign up to set email alerts
|

First-Year Doctor of Physical Therapy Students Demonstrate Change in Coping With Stress

Abstract: Background and Purpose. Admission to a Doctor of Physical Therapy (DPT) program has traditionally required a determined cognitive level with less emphasis being placed on noncognitive attributes. It is now appreciated that many noncognitive factors such as coping self-efficacy, resilience, and emotional intelligence can factor into students' ability to successfully complete a graduate program that presents with increased workload and other demands that can invoke stress. To maximize success, studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 24 publications
8
30
0
Order By: Relevance
“…A strong theme throughout the open responses was that curriculum coursework within the program and examinations caused heightened levels of stress. Students reported periods of stress with coursework and course load commitments, which is in line with previous research 3,12,14,18,23,24 conducted on undergraduate and pre-registration postgraduate students in several countries including Australia, USA, Israel and Sweden. Students frequently reported that their social life was lacking, along with time to undertake their hobbies due to workload and demands of the program.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…A strong theme throughout the open responses was that curriculum coursework within the program and examinations caused heightened levels of stress. Students reported periods of stress with coursework and course load commitments, which is in line with previous research 3,12,14,18,23,24 conducted on undergraduate and pre-registration postgraduate students in several countries including Australia, USA, Israel and Sweden. Students frequently reported that their social life was lacking, along with time to undertake their hobbies due to workload and demands of the program.…”
Section: Discussionsupporting
confidence: 89%
“…These results are in contrast to previous research. A previous study reported by Van Veld et al 3 , conducted in the United States, found changes in CSE scores over time in rst year DPHTY students. This difference between studies could be due to a variety of factors including timing of placement blocks, the curriculum coursework demands as well as the structure of the different programs.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations